Loss of heterozygosity in 7q myeloid disorders: clinical associations and genomic pathogenesis - Jerez, Andres (American Society of Hematology, 2012)
Loss of heterozygosity affecting chromosome 7q is common in acute myeloid leukemia and myelodysplastic syndromes, pointing toward the essential role of this region in disease phenotype and clonal evolution. The higher resolution offered by recently developed genomic platforms may be used to establish more precise clinical correlations and identify specific target genes. We analyzed a series of patients with myeloid disorders using recent genomic technologies (1458 by single-nucleotide polymorphism arrays [SNP-A], 226 by next-generation sequencing, and 183 by expression microarrays). Using SNP-A, we identified chromosome 7q loss of heterozygosity segments in 161 of 1458 patients (11%); 26% of chronic myelomonocytic leukemia patients harbored 7q uniparental disomy, of which 41% had a homozygous EZH2 mutation. In addition, we describe an SNP-A–isolated deletion 7 hypocellular myelodysplastic syndrome subset, with a high rate of progression. Using direct and parallel sequencing, we found no recurrent mutations in typically large deletion 7q and monosomy 7 patients. In contrast, we detected a markedly decreased expression of genes included in our SNP-A defined minimally deleted regions. Although a 2-hit model is present in most patients with 7q uniparental disomy and a myeloproliferative phenotype, haplodeficient expression of defined regions of 7q may underlie pathogenesis in patients with deletions and predominant dysplastic features.